General Description of Pharmaceutical Tablet Punching Machine: An Overview - Desai, Sushma; Gangadi, Jayapal Reddy; Baru, Chandrasekhara Rao (Advanced Concepts in Pharmaceutical Research Vol. 7, 2024)
This study described a general description of pharmaceutical tablet punching machine. Making a pharmaceutical tablet is a challenging process. You must combine the active medicinal ingredient in the correct dosage with other necessary materials and press it into a tablet. A pharmaceutical tablet press machine does this process. Tablet press tool since its invention 19 century improving the efficiency of the basic model by studying various parameters, overcoming their problems and developing into a fully automated machine meeting the demands of high quality with low cost medicines production in time to ever-growing population, complying with cGMP (current good manufacturing practices) cleanliness standards, multiple ailments. Every pharmacy institution plans to have either of the tablets punching machine for sure. The tablets may be described as a compressed solid pharmaceutical unit dosage form. they stand unique among all the pharmaceutical formulations as a tamper proof preparation. Different manufacturers customize the amount of punches, stations, compression points, and speed of their tablet presses. Therefore, it is necessary to learn about pharmaceutical tablet punching machines, including how they operate and what kinds of tablets can be made using them using any one of the three recognized methods—direct compression, wet granulation, or compression granulation—or a combination of them. The common tableting process defects caused and to overcome these problems by the tablet press tooling and performance to be evaluated parameters are studied to estimate the working efficiency of the machine at every stage with the help of ISTMs (instrumented single tablet punching machine), IRTMs (instrumented rotary tablet punching machine) investigated with the achieved data is interpreted for selection of suitable tablet press to work on.